Overview of Work Stress Among Nurses in Hospitals - Prima, Irenne Agil; Pramana, Yoga; Mita, Mita (Universitas Tanjungpura, 2024)
Background: Work stress is a critical issue in nursing that can impact productivity, performance, and overall well-being. Understanding the levels and factors associated with work stress among nurses can help in developing effective management strategies.Objective: To describe the levels of work stress and their association with demographic and professional characteristics among nurses in a hospital in West Kalimantan.Methods: This quantitative, descriptive cross-sectional study was conducted from May 12 to 14, 2023, involving 85 nurses working in inpatient wards. Data were collected using a structured questionnaire and analyzed using descriptive statistics with SPSS software.Results: Most respondents (75.3%) experienced normal levels of work stress, while 23.5% reported mild stress, and 1.2% experienced moderate stress. The majority of respondents were female (76.5%), aged 26